Tsunami Assessment for Inundation Risk Management at Chabahar Bay Facilities in Iran - Mahmood Reza Akbarpour Jannat; Ehasn Rastgoftar; Toshyuki Asano (International Journal of Coastal and Offshore Engineering, 2017)
In this study two numerical models, one a regional generation and propagation model and the other an inundation model, have been applied to the problem of examining the impact that a large, locally generated tsunami could have on Chabahar Bay facilities in Iran. To achieve a realistic outlook of tsunami hazards in the area, the generation, propagation and interaction of tsunami waves with Chabahar Bay coasts is being numerically modeled for specific events. The modeling is performed using the numerical code which solves the nonlinear Boussinesq wave equations. Results of numerical simulations performed in this study considering past tsunami occurrence records indicate that the multipurpose Chabahar Port is expected to experience the tsunami events with heights ranging between 8 to 10 meters. The model gives approximately the observed maximum area of flooding of Chabahar City. The large amount of flooding of Chabahar city coasts, Iran from the 9.1 magnitude earthquake and small amount of flooding from the 8.3 magnitude earthquake achieved and extensively flooding Chabahar City was reproduced by the numerical model. The effect of the tide was modeled and found to be small. The results of this study are intended for emergency planning purposes. Appropriate use would include the identification of evacuation zones. The results are used also to find a best configuration advice for the urban facilities in order to mitigate tsunami related risks, with positioning such facilities at the Western Cape of the bay.